Stance-taking using lexico-grammatical features in argumentative writing of Malaysian undergraduates - Lee, Geok Imm; Wong, Bee Eng; Chan, Swee Heng; Abdullah, Mardziah Hayati (Universiti Putra Malaysia Press, 2014)
Argumentative writing is an important skill expected of all students from the institutions of higher learning. These tertiary students are often required to state their opinions and put forward their arguments in their written essays, assignments, and projects. As Shannon (2011) points out students are required to write to fulfill their academic course requirements. Hyland (2005) also emphasises the importance of writing which involves interactions between writers and readers. The ways that the writers express their opinions to the readers are very much related to the choices of their language use. Therefore, this study explores how undergraduate writers state their stances in English argumentative essays. The analysis of the argumentative essays for stance was based on the framework proposed by Biber (2006), focusing on the lexico grammatical features. The findings of this study were obtained from the argumentative essays of thirty undergraduate writers from a public university in Malaysia. The findings of this study have provided a more in-depth understanding of how stance-taking can be identified through the use of particular linguistic features such as modal verbs, stance adverbs, and stance complement clauses in argumentative writing by these ESL undergraduate writers. Further, the findings from the analysis of the use of linguistic features in English for stating stances can then be used to guide these writers improve their abilities to write for academic purposes, specifically in argumentative writing.